Effect of Physical Activity on Self-Concept: Theoretical Model on the Mediation of Body Image and Physical Self-Concept in Adolescents - Juan Gregorio Fernández-Bustos; Álvaro Infantes-Paniagua; Ricardo Cuevas; Onofre Ricardo Contreras (Frontiers in Psychology, 2019)
Objective: The aim of this research was to study the mediation of body dissatisfaction, physical self-concept, and body mass index (BMI) on the relationship between physical activity and self-concept in adolescents.Materials and Methods: A sample of 652 Spanish students between 12 and 17 years participated in a cross-sectional study. Physical self-concept and general self-concept were assessed with the Physical Self-Concept Questionnaire (CAF), body dissatisfaction with the Body Shape Questionnaire (BSQ), and physical activity was estimated with the International Physical Activity Questionnaire (IPAQ-SF). BMI was utilized as a measurement of body composition. Structural equation modeling was used to assess the results.Results: The resulting models showed good fit indexes. Final model for all participants explained the 17% of the variance of body dissatisfaction, 57% of physical self-concept, and 60% of general self-concept. Physical activity had a positive and indirect effect on self-concept (β = 0.29, p < 0.01) and direct effects on body dissatisfaction (β = −0.26, p < 0.01) and physical self-concept (β = 0.20, p < 0.01). BMI had a direct effect on body dissatisfaction (β = 0.31, p < 0.01) and on physical self-concept (β = −0.10, p < 0.01) and an indirect effect on general self-concept (β = −0.24, p < 0.01). However, it was only associated with physical activity in males, playing a mediating role between physical activity and body dissatisfaction.Conclusion: Physical activity can help individuals to achieve a positive self-concept and promote psychological well-being in adolescents through the improvement of physical perceptions and body satisfaction. The importance of BMI, body dissatisfaction, and physical self-concept on the configuration of the self-concept is also emphasized. Educational policymakers and Physical Education teachers should implement strategies to promote physical activity in the schools and provide a Quality Physical Education programs to increase physical activity during adolescence.